Research and design in dual network scheme of power corporation based on network isolation and secure data exchange - Jing WANG; Kunlun GAO; Bo ZHANG (Dianxin kexue)
It is a common concern for power enterprises of how to ensure the safety and stability of power production management and information network for group-oriented power generation enterprises.The dual-network architecture of group-type power generation enterprise was designed based on network isolation and the safe data exchange technology.Based on the protection of network security isolation,the private protocol interaction technology was introduced to meet the growing business development needs of power enterprises.The overall technical route of logical strong isolation was proposed,the design scheme of construction of information internal and external network,the application and deployment,and information exchange in typical application scenarios was put forward.In addition,in order to realize the centralized monitoring and unified protection after isolation,the design scheme of deploying unified monitoring,unified anti-virus,unified terminal management and unified authentication system was put forward.